1985
DOI: 10.2135/cropsci1985.0011183x002500030025x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Two Races of Leaf Rust in Dry Edible Bean1

Abstract: A study was conducted to determine the inheritance of resistance to races 44 and 52 of leaf rust (causal organism Uromyces appendiculatus (Pers. ex Pers.) linger var. appendiculatus) in the dry edible bean (Phaseolus vulgaris L.) cultivars ‘T‐39,’ ‘Aurora,’ and ‘Olathe.’ T‐39 and Aurora each express hypersensitive resistance to race 52 but are susceptible to race 44. Olathe is hypersensitive resistant to race 44 and susceptible to race 52. Crosses were made between these cultivars and with ‘UI‐114,’ a pinto be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Major dominant genes control rust resistance (Grafton et al 1985;Stavely 1990). Pastor-Corrales et al (2001) and Stavely et al (1997) reported pinto been breeding lines that were developed under the leadership of Dr. J.R. Stavely at the USDA-ARS, Beltsville, Maryland through inter-institutional and inter-disciplinary collaborative conversion program whereby highly photoperiod sensitive rust resistant tropical and subtropical germplasm were converted to adaptation to the USA common bean growing environments over several years.…”
Section: Resultsmentioning
confidence: 99%
“…Major dominant genes control rust resistance (Grafton et al 1985;Stavely 1990). Pastor-Corrales et al (2001) and Stavely et al (1997) reported pinto been breeding lines that were developed under the leadership of Dr. J.R. Stavely at the USDA-ARS, Beltsville, Maryland through inter-institutional and inter-disciplinary collaborative conversion program whereby highly photoperiod sensitive rust resistant tropical and subtropical germplasm were converted to adaptation to the USA common bean growing environments over several years.…”
Section: Resultsmentioning
confidence: 99%
“…Single dominant 'BelDakMi-RMR-14' -to '-18' Grafton et al 1985;Stavely and Kelly 1996;Kelly et al 1996;Stavely et al 1998Stavely et al , 1999a Ur-6…”
Section: Race-specific Resistance Conferred By Major Genesmentioning
confidence: 99%
“…< ''6,5'', wide variation 'BelDakMi RR-1,' 'BelDak-RR-2', 'BelNeb-RR-1' Grafton et al 1985;Stavely 1984a;Stavely and Grafton 1989;Stavely et al 1989a,b;1994b;Kelly et al 1996 Ur-7…”
Section: Race-specific Resistance Conferred By Major Genesmentioning
confidence: 99%
See 2 more Smart Citations